Effects of Curcuma longa L. on antibody titer and body weight of sheep post vaccination for house and mouth diseases - Hasibuan, Anggiriani Mutiara Sari; Widjaja, Sry Suryani; Lubis, Inke Nadia D. (The International Journal of Tropical Veterinary and Biomedical Research, 2024)
Foot and mouth disease (FMD) is an acute and highly contagious viral infectious disease in even/split-hoofed animals and some wild animals. Diseases of the mouth and hoof can cause significant economic losses due to declining production and become an obstacle to the trade in animals and their products. FMD causes much harm to infected animals, one of which is weight loss. Vaccination is the most critical factor in the control of FMD, and the type and quality of vaccines available play an essential role. However, immunomodulators are also needed to increase the immune response to the current FMD vaccine. It is reported that administering Curcuma longa to experimental animals could increase body weight gain and immunity by increasing antibody titers. Therefore, this article will review the immunomodulatory properties of Curcuma longa about FMD infection.